Studying the Retention of Multivalent Pollutants in Bentonite - Isra Sulyman Faiez Maraaba (My University, 2014)
Radionuclides, even in low concentration, form a potential threat to the environment and, therefore, to humans due to their strong radiation and long half-life times. Water sources are among the targets of contamination by radionuclides. However, for protection of the environment, the removal and recovery of such pollutants represent an important issue of special interest. Adsorption of pollutants on a solid matrix is an effective method used for heavy metal removal from aqueous solutions. In many countries such as Sweden, Canada, France, Spain, Japan etc., the design of radioactive repositories in clay sediments is based on the combination of natural and man-made barriers to gain long-term isolation of nuclear waste. One strong alternative is to put the nuclear waste into copper containers embedded in bentonite and are placed underground. In this work, the focus is on studying the retention of multivalent pollutants in bentonite clay. The sorption of trivalent and tetravalent radioactive pollutants from sea water on bentonite has been studied using Grand canonical Monto Carlo simulation. Primitive model has been adopted where the water is included by its dielectric constant. Series of simulations have been performed with systematic variations of different parameters to investigate the sorption behavior of the system; these parameters including concentration of multivalent ion in the bulk solution, surface charge density of the plates, valency of radioactive ions, temperature of the system and ionic strength. As a result of this study, the average concentration of multivalent ions in electrical double layer and the retention coefficient are found to be strongly affected by aforementioned parameters. Specifically, the average concentration of multivalent ions in the electrical double layer was found to be increased by increasing the surface charge density, the bulk concentration of radioactive ions and the valency. However, this average concentration was found to be decreased by increasing temperature and ionic strength. On the other hand, the retention coefficient was found to be decreased by increasing the bulk concentration of multivalent species, ionic strength and temperature, although it shows incremental behavior by increasing surface charge density and valency. The predictions of this study about the sorption behavior of multivalent ions well agrees with several experimental results.

الأيونات المشعة و ان كانت بتركيز قليل تشكل خطرا على البيئة و خاصة على الإنسان و ذلك بسبب إشعاعاتها القوية وطول فترة نصف العمر. المياه من ضمن الأشياء التي لوثتها المواد المشعة. إحدى الطرق لتنقية المياه هو استخدام الماصات الصلبة لإزالة الملوثات النووية. في كثير من الدول مثل السويد وكندا وفرنسا واسبانيا واليابان يقوم تصميم المستودعات النووية في الطين على أساس الجمع بين الحواجز الطبيعية والحواجز الصناعية للحصول على عزل طويل المدى للملوثات النووية. إحدى الطرق هي وضع النفايات النووية في وعاء من النحاس ثم طمره في طينة البنتونيت تحت الأرض. في هذا العمل تم التركيز على دراسة امتصاص الملوثات النووية ثلاثية و رباعية التكافؤ بواسطة طينة البنتونيت باستخدام "جراند كانونيكال مونت كارلو محاكاة"(Grand Canonical Monte Carlo simulation) .تم تبني النموذج البدائي الذي يمثل فيه الماء بواسطة ثابت العزل الكهربائي. العديد من دراسات المحاكاة (simulation) نفذت لعدد من المتغيرات في النظام من اجل دراسة أثر تغير تركيز المواد المشعة في الماء وكثافة الشحنة السطحية للبنتونيت وشحنة المواد المشعة ودرجة حرارة النظام والقوة الأيونية على قدرة البنتونيت على امتصاص المواد المشعة. ونتيجة لهذه الدراسة وجد أن متوسط تركيز الأيونات المشعة في الطبقة المزدوجة الكهربائية(electrical double layer) و معامل الامتصاص يتأثران بقوة بالمتغيرات الآنفة الذكر. وبالتحديد وجد أن متوسط تركيز الأيونات المشعة في الطبقة المزدوجة الكهربائية تزداد مع زيادة كثافة الشحنة السطحية للبنتونيت وتركيز الأيونات المشعة في المحلول وشحنتها. بينما متوسط تركيز الأيونات في الطبقة المزدوجة الكهربائية يقل مع زيادة درجة الحرارة و القوة الأيونية. ومن جهة أخرى وجد ان معامل الإمتصاص يقل مع زيادة تركيز الأيونات المشعة في المحلول ومع القوة الأيونية ودرجة الحرارة. غير ان معامل الإمتصاص يظهر سلوكا متزايدا مع زيادة كثافة الشحنة السطحية وشحنة المواد المشعة. وهذه التنبؤات حول سلوك امتصاص المواد المشعة تتوافق بشكل جيد مع العديد من النتائج التجريبية وأحيانا تظهر عدم توافق مع نتائج تجريبية أخرى.
دراسة الاحتفاظ بالملوثات المتعددة الشحنة في طينة البنتونيت